2001
DOI: 10.3171/jns.2001.95.5.0883
|View full text |Cite
|
Sign up to set email alerts
|

Failure of low-dose radiosurgery to control temporal lobe epilepsy

Abstract: Radiosurgical treatment of intractable epilepsy has emerged as a noninvasive alternative to resection. Although gamma knife surgery (GKS) reportedly is effective when the radiation dose is sufficient to cause a destructive reaction in the targeted medial temporal lobe, the optimal target area and dose distribution are largely unknown. Some investigators have suggested that focused irradiation from a nondestructive dose is also effective. In this article the authors report two cases of medial temporal lobe epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 14 publications
0
50
1
1
Order By: Relevance
“…On the other hand, in humans, seizure remission after RS of other epileptic lesions-hypothalamic hamartomas or vascular malformations-does not require radiologic changes consistent with radionecrosis. 33,34 Similarly, histopathology of hippocampal specimens obtained from open temporal lobectomy after failed RS for MTLE 1,3,7 demonstrates perivascular sclerosis and hyalinization, rather than necrosis. However, since these specimens were obtained from unsuccessful RS, they may not be sufficient to explain the changes required for successful RS in MTLE.…”
Section: Fluid-attenuated Inversion Recovery Coronal (A-e) T1 Coronamentioning
confidence: 99%
“…On the other hand, in humans, seizure remission after RS of other epileptic lesions-hypothalamic hamartomas or vascular malformations-does not require radiologic changes consistent with radionecrosis. 33,34 Similarly, histopathology of hippocampal specimens obtained from open temporal lobectomy after failed RS for MTLE 1,3,7 demonstrates perivascular sclerosis and hyalinization, rather than necrosis. However, since these specimens were obtained from unsuccessful RS, they may not be sufficient to explain the changes required for successful RS in MTLE.…”
Section: Fluid-attenuated Inversion Recovery Coronal (A-e) T1 Coronamentioning
confidence: 99%
“…Previous studies have reported that a low radiation dose (< 20 Gy) is often associated with the failure of GKRS to control seizures and a lack of MRI changes 9 and that a higher dose causes greater clinical effects and radiological changes. 4 In our present study, we used the previously documented effective treatment dose of 24 Gy to the residual tissue of the presumed epileptogenic zone, although the target volume was lower than in previous studies (range 1.8-6.9 cm 3 vs 5.5-9 cm 3 ) that used GKRS as an initial surgical treatment in patients with MTLE-HS.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, resective surgery was also performed following GKRS because of insufficient treatment effect, and most patients became seizure-free immediately after open surgery. 3,13,25,30,36) Furthermore, delayed seizure control of GKRS exposes patients to many risks such as injury, drowning, or unexpected death associated with seizure. 22) Immediate cessation of seizure seems to decrease mortality after epilepsy surgery.…”
Section: Discussionmentioning
confidence: 99%
“…2) However, some studies reported that none of the patients became seizure-free after GKRS. 13,30,36) To date, the seizure outcome in patients with MTLE after GKRS has not been consistent. 22) In the studies with good seizure outcome, non-invasiveness and safety were emphasized as major advantages of GKRS over resective surgery.…”
Section: Introductionmentioning
confidence: 99%